Implementing of the Aptitude Treatment Interaction (ATI) Learning Model for Linear Equation Systems and Matrix Materials for Prospective Mathematics Education Teacher Students - Lailin Hijriani; Meiva Marthaulina Lestari Siahaan; Gusti Firda Khairunnisa; Emily Johnson (RANGE: Jurnal Pendidikan Matematika, 2024)
ABSTRACT This study aims to see the learning outcomes of prospective mathematics education teacher students after applying the Aptitude Treatment Interaction (ATI) learning model for linear equation systems and matrix. This study uses a quantitative descriptive approach with data collection techniques are test and documentation. Subjects were grouped into three categories, namely subjects with high mathematical abulity, medium, and low mathematical ability. The results showed that the application of the Aptitude Treatment Interaction (ATI) learning model gave a good response to learning outcomes with an average of 78.10 in the good category. This can be seen from the student learning outcomes as a whole, both students with high mathematical ability, medium, and low mathematical ability. So, it can be concluded after applying the Aptitude Treatment Interaction (ATI) learning model that the overall intake of students when viewed from their mathematical abilities does not cause a wide gap between them.